AutoCAD LT for Windows 95 basics through advanced - Madsen, David A. (Prentice Hall, 1998)
Designed in the format of a text workbook, this work takes students through the systematic use of AutoCAD LT with emphasis on the proper use of drafting standards in several key disciplines. It is suitable for design drafting programs such as mechanical, architectural and electrical drafting, and graphic design programs, where AutoCAD LT is used.